PHYTOCHEMICAL CONSTITUENTS AND BIOLOGICAL ACTIVITIES OF HOMALIUM ZEYLANICUM BENTH. - RACHALA VINOD KUMAR; KATAKAM BABITHA; NIRANJAN KUMAR; KVNS SRINIVAS; J KOTESH KUMAR; SHAILENDRA PRATAP SINGH; PARAMJIT GROVER (International Journal of Pharma and Bio Sciences, 2014)
Homalium zeylanicum is a rare and phytochemically less explored tropical tree. Chemical examination of bark and leaf of this species yielded phenolic compounds 3-Phenyl coumarin (1) and 4’-O-Methyl-Epigallo catechin (2). The structures of the compounds were established on the basis of various NMR spectral data. The extracts of bark, leaf and their isolated compounds showed both antioxidant and anticancer activities in in vitro mode. The acetate derivative of compound 2 showed significant anticancer activity against human cancer cell line IMR-32 (IC50 6.26 µg/ml) in the MTT assay.